Peran Tenaga Kependidikan dalam Meningkatkan Efektivitas Layanan Akademik Kesiswaan di SMK Muhammadiyah 2 Palembang - Jefri Yansyah Hadiwinoto; M. Hasbi; Sri Eva Mislawati (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the role of educational staff in improving the effectiveness of student academic services at SMK Muhammadiyah 2 Palembang. The research was motivated by the importance of educational staff in supporting academic administration and student services to ensure the effectiveness of educational activities. This study employed a qualitative descriptive approach. Data were collected through interviews, observations, and documentation involving the head of administration, administrative staff, and students as informants. The data were analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings indicate that educational staff have played a significant role in improving the effectiveness of student academic services through student data management, attendance administration, grade archiving, grade promotion administration, academic and non-academic activity assistance, academic information dissemination, and special services for students requiring additional support. The quality of services provided by educational staff was found to be effective based on the dimensions of reliability, responsiveness, assurance, empathy, and tangibles. Although several challenges were identified, such as frequent student data updates, administrative workload, and the need for coordination among stakeholders, these issues were addressed through systematic administration, regular data verification, and collaboration with teachers, counselors, and parents. Therefore, educational staff contribute significantly to creating effective, organized, and student-oriented academic services that support the achievement of educational objectives at the school.